POLITICAL DIRECTION OF DIGITAL TRANSFORMATION LAW IN THE CRIMINAL JUSTICE SYSTEM (E-LITIGATION) TO REALIZE THE PRINCIPLES OF SIMPLE, FAST, AND LOW-COST JUSTICE - Andre Firza Setyananda; Lucky Ferdiles (MALA IN SE: Jurnal Hukum Pidana, Kriminologi, dan Viktimologi, 2026)
Digital transformation in the criminal justice system is a necessity along with the increasingly massive development of information and communication technology. One of the concrete forms of this transformation is the implementation of the e-litigation system in the criminal justice process. The presence of e-litigation is not only interpreted as an administrative technical innovation, but also as a manifestation of the political direction of national law in building an effective, efficient, and fair judicial system. This article aims to analyze the political direction of digital transformation in the criminal justice system in Indonesia and examine its relevance to the principles of simple, fast, and low-cost justice. This research uses normative juridical methods with legislative, conceptual, and historical approaches. The results of the study show that the implementation of e-litigation in the criminal justice system is a form of progressive legal policy that aims to strengthen access to justice, increase transparency, and reduce structural barriers in the criminal law enforcement process. However, the effectiveness of e-litigation still faces various challenges, both in terms of regulations, the readiness of law enforcement officials, and the technology gap in society. Keywords: Legal politics, digital transformation, e-litigation, criminal justice, judicial principles.